Dimensões do poder e império: a legitimação das violências biopolíticas - Chini, Mariana (2020)
This dissertation is part of the Social Relations and Dimensions of Power Research Line, and its scientific objective is to analyze the problem of how the exercise of power and its dimensions work in the paradigm of the Empire and how the legitimization of its biopolitical project operates. As for the methodology, it is based on the operational logic of the hypothetical-deductive method, with a qualitative approach, with bibliographic and eventually documentary technical procedures. It has two initial hypotheses and three specific objectives that aim to examine them. Initially, it approaches the relationship between law, the modern State and capitalism (using some key theories and concepts of Max Weber) as well as contractualist theories, tending towards the concept of the modern State and the problem of violence in this form of State. Then, it determines what the dimension of globalized power called Empire consists of - drawing distinctions between it and imperialism - and also indicating the locus of its manifestation. Finally, it examines the legitimization of biopolitical violence - both in the sphere of new forms of production based on immaterial labor, and of the Empire as a legal proposal - as well as the search for an alternative to liberate oneself from this violence. As a result, it is found that the functioning of the exercise of power and its dimensions in the paradigm of the Empire occurs both without limitation of the sovereign right of the State - due to the erosion of modern delimitations for the exercise of political and legal power - and in a State of permanent exception, where sovereign decision is pulverized; and the legitimization of the exercise of power in this new globalized dimension derives from a cultural establishment project established by the Empire - which would aim to deceive the "bios", that is, it would manipulate and control individuals -, but also through a bio and necropolitical control whose main objective would be the destruction of the "bios", in the sense of annihilation/extermination/death of individuals. However, one can also perceive the possibility of using imperial legal processes to create horizons of liberation that enable individuals to escape from the imperial non-place by taking possession of this indeterminate space through a collective, such as the multitude.